Hypomagnesemia and cause-specific mortality in hemodialysis patients: 5-year follow-up analysis - Selim, Gjulshen N.; Spasovski, Goce; Tozija, Liljana; Georgievska-Ismail, Ljubica; Zafirova Ivanovska, Beti; Masin-Spasovska, Jelka; Rambabova Bushljetic, Irena; Petronijevic, Zvezdana; Dzekova Vidimliski, Pavlina; Ristovska, Vesna; Pushevski, Vladimir; Stojcheva Taneva, Olivera (SAGE Publications, 2017)
The aim of this prospective study was to evaluate the association between serum magnesium (Mg) and mortality, in particular the cause-specific mortality of Mg and other risk factors in hemodialysis (HD) patients.
Keywords: C-reactive protein; cardiovascular risk; hemodialysis; inflamation; magnesium